2006
DOI: 10.1097/01.wad.0000201851.52707.c9
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and Proxy-Reported Utility in Alzheimer Disease Using the EuroQoL

Abstract: This study aims to compare patient- and proxy-rated utilities and health-related quality of life from individuals in different stages of Alzheimer disease (AD). Two hundred seventy-two patients and their primary caregivers were enrolled in a prospective observational study and underwent three consecutive interviews, 6 months apart. Average Mini-Mental State Examination (MMSE) scores were 19.3, 18.0, and 16.4 at the three interviews; scores ranged from 0 to 30. Using the EuroQoL EQ-5D instrument, patient-rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
153
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(189 citation statements)
references
References 20 publications
31
153
4
1
Order By: Relevance
“…Consistent with findings by Jonsson and colleagues [11] also using the EQ 5D, self ratings of current health by patients with mild cognitive impairment in the current study tended to be higher than paired caregiver ratings when the time trade-off or rating scale assessment methods were used.…”
Section: Discussonsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with findings by Jonsson and colleagues [11] also using the EQ 5D, self ratings of current health by patients with mild cognitive impairment in the current study tended to be higher than paired caregiver ratings when the time trade-off or rating scale assessment methods were used.…”
Section: Discussonsupporting
confidence: 80%
“…They also found that the EQ 5D scores did not systematically vary with their dementia severity measure among the 137 patients studied. A larger study by Jonsson and colleagues [11] (n = 208) reports that the agreement between patients' and caregivers' scores was not lower among the more severely affected cases and that patients tended to rate their health state as being better than the (proxy) ratings given by their caregivers. This was true even among those with mild dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QoL impact of POCD was based on the utility decrement reported by Jonsson and colleagues 110 for the difference between a MMSE evaluation score of > (no dysfunction), which had a utility of 0.69, and a MMSE evaluation score of between 21 and 25 (indicating mild cognitive impairment), which had a utility of 0.64.…”
Section: Quality Of Life Impact Of Postoperative Cognitive Dysfunctiomentioning
confidence: 99%
“…Dementia patients with severe impairment and requiring more assistance during the execution of activities of daily living have a risk of death three times higher than that of older adults who perform their activities normally 50 . According to these data, patients who postpone the onset of functional impairment and mitigate neuropsychiatric disorders tend to have a lower degree of suffering due to dementia, put less strain on caregivers, and decrease their risk of mortality 51 . It is worth mentioning some methodological limitations to our study that may have weakened the findings.…”
Section: Discussionmentioning
confidence: 99%